MEMBANGUN KEPUASAN PASIEN DENGAN MENINGKATKAN SERVICE QUALITY SECARA PRIMA Di KLINIK ANISA MEDICAL CENTRE - Hayu Yolanda Utami; Rizky Natassia (Jurnal Abdimas Saintika, 2022)
Customer satisfaction is something that must be considered by service providers in order to increase the number of service users. Clinic is one of the service providers in this case is health services. In order for the services provided to be optimal, one of the efforts that must be considered by the clinical management is to improve the quality of services which include physical facilities, empathy, reliability, responsibility and assurance. These five dimensions must be considered by clinical management to increase user satisfaction of the health services it provides.